MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN MENGGUNAKAN MEDIA KARTU KATA BERGAMBAR PADA ANAK KELOMPOK B DI TK ISLAM MASHITA GOWA - Amelia Putri; Tasrif Akib; Nur Alim Amri (Jurnal Riset Guru Indonesia, 2022)
This study aims to find out whether using picture word card media can improve early reading skills in early childhood in Mashita Gowa Islamic Kindergarten. This type of research is classroom action research (Classroom Action Research) which consists of two cycles each cycle there are three meetings. Research procedures include planning, implementation, observation, and reflection. The subjects in this study were group B children of Mashita Gowa Islamic Kindergarten, as many as 18 children. The results of this study can be concluded That the increase in the first cycle of meetings I, II, and III of students is at the level of MB development (Starting to Develop) with an average value of 36.54%. Furthermore, cycle II of meetings I, II, and III was carried out so that there was an increase to 84.37%, which means that the average child is already at the level of BSB development (Very Good Development). Based on the results of the research above, it was concluded that there was an improvement in the ability to read the beginning of children in Mashita Gowa Islamic Kindergarten Group B after using the medium of picture word cards.